Long‐Term Electrical and Mechanical Function Monitoring of a Human‐on‐a‐Chip System. (14th December 2018) - Oleaga, Carlota; Lavado, Andrea; Riu, Anne; Rothemund, Sandra; Carmona‐Moran, Carlos A.; Persaud, Keisha; Yurko, Andrew; Lear, Jennifer; Narasimhan, Narasimhan Sriram; Long, Christopher J.; Sommerhage, Frank; Bridges, Lee Richard; et al.
Abstract: The goal of human‐on‐a‐chip systems is to capture multiorgan complexity and predict the human response to compounds within physiologically relevant platforms. The generation and characterization of such systems is currently a focal point of research given the long‐standing inadequacies of conventional techniques for predicting human outcome. Functional systems can measure and quantify key cellular mechanisms that correlate with the physiological status of a tissue, and can be used to evaluate therapeutic challenges utilizing many of the same endpoints used in animal experiments or clinical trials. Culturing multiple organ compartments in a platform creates a more physiologic environment (organ–organ communication). Here is reported a human 4‐organ system composed of heart, liver, skeletal muscle, and nervous system modules that maintains cellular viability and function over 28 days in serum‐free conditions using a pumpless system. The integration of noninvasive electrical evaluation of neurons and cardiac cells and mechanical determination of cardiac and skeletal muscle contraction allows the monitoring of cellular function, especially for chronic toxicity studies in vitro. The 28‐day period is the minimum timeframe for animal studies to evaluate repeat dose toxicity. This technology can be a relevant alternative to animal testing by monitoring multiorgan function upon long‐term chemical exposure. Abstract : Human multiorgan in vitro platforms are designed to reproduce human in vivo complexity in vitro, reducing the need for animal experimentation and improving human prediction. Incorporating functional readouts into these systems enables closer approximation to clinical measurements, reducing the need for traditional biochemical metrics. Establishing a long‐term multiorgan platform enables studying chronic drug administration, currently difficult for in vitro models.